Improving Mechanical Properties of Polymer Modified Steel Fiber Reinforced Concrete Made with Concrete Waste by usingPC-600-Super-Plasticizer - Jabal, Qusay A.; Almusawi, Jenan N.; Sharba, Niran M.; Rasool Alasadi, Layth Abdul (Journal of Research Updates in Polymer Science, 2025)
This study investigates the enhancement of mechanical properties in polymer-modified steel fiber-reinforced concrete (PMSFRC) incorporating demolition waste as a sustainable coarse aggregate replacement. The work addresses the dual objectives of resource recycling and performance optimization within environmentally responsible construction practices. Results show that replacing natural coarse aggregates with demolition waste slightly reduces compressive strength from 44.1 MPa to 41.6 MPa. However, the incorporation of PC-600 Flocrete superplasticizer effectively compensates for this reduction, increasing compressive strength to 49.4 MPa. Significant improvements were also observed in tensile strength, which increased from 5.7 MPa to 6.1 MPa, and in flexural strength, which increased from 12.1 MPa to 15.5 MPa for mixes with 100% waste replacement. Additionally, the modulus of elasticity improved from 26.5 GPa to 30.5 GPa, demonstrating enhanced stiffness and structural viability. These findings confirm that polymer modification enables effective utilization of concrete waste without compromising structural integrity, promoting cleaner production, circular material use, and sustainable innovation in civil infrastructure.